Optimasi Keuntungan Bisnis Cilok Menggunakan Program Linear Metode Simpleks - Siregar, Salsa Dea Oktavianda; Harahap, Rini Rizkyana; Ritonga, Irmayanti (Universitas Labuhanbatu, 2024)
The aim of this research is to find out whether the product produced can provide maximum profits from the sale of cilok and to find out what variables hinder optimum value in the cilok business so mathematical modeling can be created using a simplex method linear program. Cilok is a business that operates in the culinary sector, namely food made from various ingredients, with the main ingredients being tapioca flour and wheat flour. Cilok is round in shape like meatballs, only the basic ingredients are different. Cilok has various filling variants, one of which contains chicken meat and some that don't use any filling. As for the complementary ingredients, namely peanut sauce, soy sauce and sauce, it is a problem that if one of these ingredients is not fulfilled then production in the cilok business will be hampered. From the research results, it is known that the optimal input combination provides a profit of IDR 320,000.00/day.